Effect of Gel Formulation of Corn Silk Extract (Stigma Maydis) On Burn Wound Healing In Male White Rat - Nessa, Nessa; Putri, Noni Rahayu; Fitrianda, Eka; Elmitra, Elmitra; Asra, Ridho (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: Burns are damage or loss of tissue caused by exposure to very high temperatures. This study was to determine the effect of gel formulation from corn silk (Stigma maydis) in healing burns in male white rats. Data Sources Study Selection: This research is an experimental research of the effect of gel formulation from corn silk (Stigma maydis) in healing burns in male white rats Summary of contents of the article: Five groups are used in this study. Group I (induced hot metal), group II (induced hot metal + gel base), group III (induced hot metal + 10% corn silk extract gel), group IV (induced hot metal + 15% gel of corn silk extract gel), group V (induced hot metal + B® gel). Observations were made for 21 days. The results of this study are the average % of burns healing on day 7, 14 and 21 : group I (27.29%, 63.03%, 100%), group II (35.39%, 60.16 %, 100%), group III (37.16%, 65.34%, 100%), group IV (36.89%, 68.23%, 100%), group V (32.81%, 66, 48%, 100%). The period of epithelialization of skin tissue are groups I, II, III on day 16, group IV on day 14 and group V on day 17. The mean results of the epithelialization scores for groups I, II, III, IV and V (2, 2, 3, 3, 3), the mean fibroblast score results (2,7, 2,9, 3, 3, 3), groups I, II, III, IV and V collagen fiber density groups I, II, III , IV and V (2,2, 2,8, 3,6, 3,9, 3,9). The two-way ANOVA statistical analysis test on % burn healing was not significant (p> 0.05), and the one-way ANOVA statistical analysis test at the period of epithelialization was not significant (p>0.05) and the histology of epithelialization and fibroblasts was not significant (p>0.05), the density of collagen fibers was significant (p<0.05). Conclusion: The conclusion of this study is corn silk extract gel (Stigma maydis) 10% and 15% have the effect on the healing process of burns and can be formulated in gel dosage forms.